Quality of Coffee canephora var Robusta as affected by the proportion of overripe berries. - Geronimo, Ande Bon B. (c2005)
Coffea canephora var. Robusta berries were used in this study to determine differences in sensory characteristics of four formulated coffe blends. In each blend, the percentage of overripe berries was varied (0%, 20%, 25% and 30%). The percentage was based on the previously determined proportion of under-ripe, ripe, and overripe berries present in harvested berries. Fiftry untrained panelists were employed for consumer acceptance and consumer preference tests. The panelists, however, were not able to significantly detect any difference among the blends. This signifies that the proportions of overripe C. canephora beans included in this study did not significantly affect the quality of the coffee. The degree of roasting could also have masked other differences in sensory quality, particularly aroma. It must be noted as well that Robusta is usually used for blending.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: coffee